Statistical analysis of religious conversion testimonies - Alpysbay, M.; Utebayeva, D.; Koishybayeva, S. (Eurasian Journal of Religious Studies, 2025)
This article is devoted to the analysis of testimonies of religious conversion in the post-Soviet space using the Conversion Impact Index (CII) method. The purpose of the study is to systematize testimonies and identify their structural patterns through statistical analysis. The main innovation of the work is that for the first time CII was used not only as a means of qualitative interpretation, but also as a basis for quantitative statistical processing. Such an approach expands the methodological possibilities in religious studies and sociology of religion. The research methodology includes coding 41 testimonials in 14 CII categories, calculating characteristic statistical indicators (mean value, standard deviation, median, mode, interquartile range) and visualizing the results (column chart, Box plot, heatmap). This approach made it possible to identify universal and context-specific features in conversion testimonials. The main results showed that rhetorical, emotional, and theological dimensions are consistently found in testimonies, while categories such as special experience, source of invitation, and professional existence are quite variable. This proves that conversion is not only an individual spiritual change, but also a process that depends on the social and cultural context. The value of the study lies in its contribution to the sociology of religion by combining qualitative and quantitative approaches. Practical significance-the results obtained can be used in interdisciplinary research in the fields of sociology, psychology and religious studies. Keywords: Religious Conversion, Conversion Impact Index (CII), Narrative, Statistical Analysis, Visualisation